QCT Reconstruction Kernel has Important Quantitative Effects on Finite Element Estimated Bone Strength - Michalski, Andrew S.; Edwards, Brent W.; Boyd, Steven K. (CMBES Proceedings, 2016)
Quantitative computed tomography (QCT) is utilized in bone imaging for quantification of volumetric bone mineral density (vBMD), bone mineral content (BMC), and bone volume. QCT is emerging as an effective tool in combination with finite element (FE) analysis to predict bone failure strength and stiffness. Bone imaging by QCT often utilizes a sharpening reconstruction kernel to produce well defined edges of the bone surface, whereas standard clinical visualization uses a medium smoothing reconstruction kernel. The effect of the reconstruction kernel on quantified measure of bone quality are unknown, but may have important effects on the final non-invasive assessment of bone strength. The purpose of this study was to determine the effects of QCT reconstruction kernel on the quantitative assessment of bone quality. We hypothesize that the QCT reconstruction kernel affects the outcome measures of vBMD, BMC, and FE predicted bone strength. Clinical QCT scans of the proximal femur were reconstructed using two representative kernels, a bone sharpening kernel and standard smoothing kernel. QCT-FE analysis was performed using a standard sideways fall loading configuration. Output measures of vBMD, BMC, bone volume, and FE predicted bone strength and stiffness were compared for each reconstruction kernel. Significant differences were found in the measures of vBMD (% Difference: -17.73%, p<0.001), BMC (% Difference: 7.98%, p<0.01), and bone volume (% Difference: -9.78%, p<0.001) between the two reconstruction kernels. This work highlights the importance of reconstruction kernel for QCT-based FE models, and needs to be considered when predicting non-invasive osteoporotic bone strength and fracture risk.